Long-term phosphodiesterase 5 inhibitor administration reduces inflammatory markers and heat-shock proteins in cavernous tissue of Zucker diabetic fatty rat (ZDF/fa/fa) - Toblli, Jorge Eduardo (2015)
Oxidative stress and nitrosative stress present in type 2 diabetes mellitus (T2DM) and metabolic syndrome (MS) induce inflammatory response in diverse tissues including cavernous tissue (CT). Heat-shock proteins (HSPs) have an important role in modulating and repairing tissue injury, although their participation in CT in T2DM is unclear. Beyond the specific action of phosphodiesterase type 5 inhibitors (PDE5i) on erectile function, it has been proposed that chronic administration of these agents improves endothelial function and ameliorates fibrotic changes. The aim of this study was to determine in CT of Zucker Diabetic Fatty (ZDF) rat, an experimental model of T2DM and MS: (1) the degree of oxidative stress and nitrosative stress; (2) the magnitude of inflammatory markers such as tumor necrosis factor-α (TNFα) and interleukin 6 (IL6); (3) immunoexpression of HSP70 and HSP27; (4) how a long-term PDE5i administration may modify these variables. For 6 months, (1) untreated ZDF; (2) ZDF+Sildenafil (Sil) and (3) control Lean Zucker Rat (LZR) received no treatment, were studied. Penises were processed for functional ´in vitro´ studies, oxidative and nitrosative stress evaluation and immunohistochemistry in CT using TNFα; IL6; nitrotyrosine, HSP70 and HSP27 antibodies. ZDF+Sil presented better relaxation in corporal strips versus untreated ZDF. Furthermore, ZDF+Sil presented less lipoperoxidation in CT versus untreated ZDF. The activity of antioxidant enzymes CuZn superoxide dismutase (CuZnSOD) and glutathione peroxidase (GPx) was also reduced in untreated ZDF in CT along with a decrease in glutathione versus untreated ZDF. Nitrotyrosine expression was increased in untreated-ZDF rats versus ZDF+Sil and LZR. TNFα and IL6 were decreased in CT in ZDF+Sil versus untreated ZDF. Additionally, the expression of HSP70 and HSP27 was reduced in CT in ZDF+Sil versus untreated ZDF. In conclusion, this study provides substantial evidence supporting a protective role of a long-term therapy with Sil on CT in a recognized animal model of T2DM and MS.